A multi-level examination of the experiences of female sex workers living with HIV along the continuum of care in the Dominican Republic. Issue 8 (3rd August 2018) - Zulliger, Rose; Kennedy, Caitlin; Barrington, Clare; Perez, Martha; Donastorg, Yeycy; Kerrigan, Deanna
ABSTRACT: Female sex workers (FSWs) are disproportionately affected by HIV, but there is limited research on their HIV care experiences. This study explored the experiences of 44 FSWs living with HIV in Santo Domingo, Dominican Republic along the HIV care continuum using in-depth interviews and focus groups. Data were analysed through narrative and thematic analysis. Individual-level factors that facilitated engagement in HIV care were physical and mental health. At the interpersonal level, disclosure of HIV or sex work status and receipt of emotional and economic support were important influences on engagement. Yet, negative reactions to or lack of disclosure of these statuses compromised engagement, further highlighting the role of stigma and discrimination. At the environmental level, FSWs described considerable challenges with the health system including long waits and treatment stock-outs at their clinics, but were generally satisfied with HIV clinic staff. At the structural level, lack of economic resources complicated care and treatment adherence. Findings underscore the need for psychosocial and economic support tailored to the unique needs of FSWs to maximise the individual and public health benefits of HIV care.